Competitiveness and redefinition industrial product (Journal of the College of Basic Education, 2022)
The research deals with the relationship between competitiveness and the re-definition of industrial products, the research problem were defineded by asking : "How can companies compete with each other through the re-definition of industrial products?".the goal of research is to: determine the competitive dimensions in light of the product re-definition . The importance of research is in highlighting the concept of product re-definition and its uses in product development . Find objective has been determined by examining the competitive dimensions of the re-definition of industrial products, through study sample of three models of household electrical appliances for three of the companies are global (Noria, Havells, MorphyRichards) and for the years between 2012-2016.. Use descriptive approach in the analysis of the sample through a form of analysis . The researcher reached a number of results, the most important of which are:The existence of the use dimension is the variety of options for use, control, and ease of use through the mechanisms of functional integration of the buttons and soft pressure mechanism.The existence of aesthetic dimension is the reduction of volume and formality and the use of modern materials in the form of the product and the approach to the appearance of electronic devices.The existence of a communicative dimension between the product and the user is the use of digital and symbolic information interfaces in the product.